Application of Complex Chitosan Hydrogels Added With Canola Oil in Partial Substitution of Cocoa Butter in Dark Chocolate - Gallegos Soto, Andres Silvestre; Rabelo, Renata Santos; Vélez-Erazo, Eliana Marcela; de Souza Silveira, Paulo Túlio; Efraim, Priscilla; Hubinger, Miriam Dupas (Frontiers in Sustainable Food Systems, 2020)
The complexation of polymeric materials can be an alternative to trapping oil in a physical network for formulating foods with reduced saturated fat content. In this research, we have evaluated the use of different polymer ratios of Sodium Alginate (ALG), Carrageenan predominance iota (CR1) and Carrageenan predominance kappa (CR2) complexed with Chitosan (CHI) at a fixed polymer concentration (2% w/v) to formulate complex hydrogels and assess their oil holding capacity. The objective was to determine the polymer ratios of CHI to anionic polysaccharides (75:25, 50:50, and 25:75), determining the oil retention capacity in different ratios, and how this can affect the stability, microstructure and rheology of to produce low saturated chocolate with trapped canola oil. The stability of the hydrogels was characterized, considering the water retention and retention of canola oil in polysaccharides complexes. The more stable system was the hydrogel CHI:CR2 in a polymer ratio of 25:75. This formulation, when added of 20% of canola oil presented an apparent viscosity of 0.631 Pa.s at 300 s−1, and its use as replacer of saturated fat allowed the production of dark chocolate with 16% reduction in fat content and 80% of added cocoa butter. Stability studies showed that polysaccharides complexes network can retain the edible oil in chocolate formulation for 60 days. It has been proven that polysaccharides complexes can be incorporated to partially replace the fatty phase in chocolates without considerable changes in relevant characteristics as consumer acceptance evaluated by sensory tests and rheological properties.